The Effect of Nighttime LED Lighting on Tomato Growth, Yield, and Nutrient Content of Fruits - Inna V. Knyazeva; Olga Panfilova; Oksana Vershinina; Alexander A. Smirnov; Alexey S. Dorokhov; Ibrahim Kahramanoğlu (Horticulturae)
Food insecurity is a top economic and national security concern in many countries, and scientists worldwide are working to increase crop productivity in order to address this issue. In line with this information, the present study aimed to test the possibility of improving the yield and fruit quality of two tomato cultivars, namely ‘Vspyshka’ and ‘Lyana’. The effect of LSL (light of sodium lamps—control) and the short additional 4 h treatment of nighttime LED lighting (LSL+night LED) with an increase in the proportion of red, blue, and far-red spectra on tomato fruit yield as well as its physiological, biochemical, and consumer attributes were compared in this study. The results suggested that LSL+night LED significantly increased soluble solids concentration, vitamin C content, and polyphenolic compounds of tomato fruits, taking into account the varietal characteristics. Moreover, a moderate to high relationship was also observed between the polyphenolic complex, vitamin C content, and antioxidant activity. It was concluded that the LSL+night LED could further enhance the relationship between polyphenols and antioxidants, as well as soluble solids concentration. LSL+night LED treatment also provided an increased accumulation of five essential amino acids associated with the taste characteristics of fruits, namely histidine, valine, threonine, licin, and the sum of isoleucine. In addition, the contents of lysine and methionine increased in the ‘Lyana’ cultivar. LSL+night LED treatment was also noted to have a less pronounced effect on the contents of aspartic acid and asparagine, as bio stimulators of plant growth processes, as well as the amino acids arginine, serine, glycine, and tyrosine, which were additionally consumed to restore photosynthesis. LSL+night LED treatment reduced the concentration of nitrates in fruits, which is a toxic element for human health. Overall, the results of the study are believed to be demanded in practical applications, with potential benefits in improving the elements of resource-saving technology for growing vegetable crops.